An Assessment of Financial Literacy and Decision Making Power among Indian Women: A Review: Exploring the Financial Literacy Level and Decision Making Power of Indian Women (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The lower level of financial literacy is one of the greatest concerns for Indian women since independence. Although our country has made noteworthy progress in this area but still a lot needs to be improved. To assess the financial literacy level of women, we conduct a survey for which, a questionnaire is prepared and distributed among the working women in the state of Rajasthan. On the basis of these responses, we assess the financial literacy level of women based on their financial knowledge, attitude and behaviour relating to their personal finances. The results of the survey show that the general awareness about financial planning tools and techniques among women remains poor even today, in 21st century. The findings suggest that women have performed comparatively better in terms of financial attitude and behaviour as compared to financial knowledge score. Also, the single women outperform married women in terms of their financial literacy score.